Cultivation of Egyptian Herbs-ammi Majus and Ammi Visnaga - Singh, V. P. (Indian Forester, 1963)
Though Ammi visnaga and Ammi majus are not pharmocoepial drugs, the formel' has come into prominence in the treatment of angina pectoris and bronchial asthma, whereas the latter is used in the treatment of leucoderma. Extracts are made out of the seeds of these species. Formerly the requirements for these species in Europe were met from Egypt, but now stoppage of export by Egypt since the last few years has given rise to an enormous unfulfilled demand. Trials of Ammi majus in Chakrata forest division have given very successful results, while useful information regarding the cultivation of Ammi visnaga has been obtained. The Ammi majus seeds produced have been put in the European market and have earned some foreign exchange. It is roughly estimated that by sale of Ammi majus grown in India, foreign exchange worth Rs. 8,00,000/- can be earned.